2021
DOI: 10.1093/advances/nmaa164
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Probiotic Supplementation for Preterm Neonates—A Systematic Review and Meta-Analysis of Nonrandomized Studies

Abstract: Systematic review and meta-analyses of randomized controlled trials (RCTs) show that probiotics reduce the risk of necrotizing enterocolitis (NEC ≥ Stage II), late onset sepsis (LOS), all-cause mortality, and feeding intolerance in preterm neonates. Data from observational studies is important to confirm probiotic effects in clinical practice. We aimed to compare outcomes before and after implementing routine probiotic supplementation (RPS) in preterm neonates (<37 weeks of gestation) by performing a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 59 publications
(56 reference statements)
0
40
0
1
Order By: Relevance
“…[35][36][37] However, it is equally possible that TS probiotic was not superior in reducing TFF compared with SS, or its effect size was smaller than expected. It is important to note that other investigators have reported TFF of 11±3.6, 38 12 (9-16) 39 and 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) 40 days in very preterm infants. Boscarino et al concluded that highenergy intake administered through the enteral route was positively correlated to cerebral growth, whereas energy intake via the parenteral route resulted in poorer cerebral growth.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…[35][36][37] However, it is equally possible that TS probiotic was not superior in reducing TFF compared with SS, or its effect size was smaller than expected. It is important to note that other investigators have reported TFF of 11±3.6, 38 12 (9-16) 39 and 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) 40 days in very preterm infants. Boscarino et al concluded that highenergy intake administered through the enteral route was positively correlated to cerebral growth, whereas energy intake via the parenteral route resulted in poorer cerebral growth.…”
Section: Discussionmentioning
confidence: 85%
“…The median TFF was comparable between the SS and TS groups (11)(12)(13)(14)(15)(16) vs 10 (IQR 8-16) days; HR 1.02, 95% CI 0.74 to 1.40; p=0.920).…”
Section: Primary Outcome (Tff: 150 Ml/kg/day)mentioning
confidence: 83%
See 2 more Smart Citations
“…Probiotics are microorganisms thought to confer a health benefit when consumed through altering the composition of the intestinal microbiota. For premature infants, they are becoming more accepted as prophylaxis against necrotizing enterocolitis ( 15 , 16 ). Indeed, evidence has shown that provision of probiotics, such as Bifidobacterium animalis lactis, B. bifidum, B. infantis, Lactobacillus acidophilus, L. reuteri , and L. rhamnosus , in preterm and term infants as well as rhesus monkey infants has a significant impact on the microbial community structure ( 4 , 17 19 ).…”
Section: Introductionmentioning
confidence: 99%